Artistic expressions of the Covid-19 Pandemic: Ideology and Otherness in the digital comic "The Wuhan I Know" by Laura Gao - Puchmüller, Andrea Bibiana (2022)
The purpose of this paper is to analyze the graphic memoir "The Wuhan I know" (Gao, 2020) that was published on the WWW and social networks during the first stage of the Covid-19 pandemic.The comic narrates the discrimination towards Asians and in particular towardsWuhanese in the United States during the pandemic. The comic is approached from a postcolonial perspective and nodal conceptual concepts such as ideology, identity, and Otherness. Umberto Eco's theory(2008) has been followed to study the structure of the comic as an ideological statement. The analytical reading concludes that in the context of the Covid-19 pandemic crisis, “The Wuhan I Know” acquires epistemic salience in a continuum of discriminatory discourses that it attempts to deconstruct.